Auxin analog-induced Ca2+ signaling is independent of inhibition of endosomal aggregation in Arabidopsis roots. (27th January 2022) - Wang, Ren; Himschoot, Ellie; Grenzi, Matteo; Chen, Jian; Safi, Alaeddine; Krebs, Melanie; Schumacher, Karin; Nowack, Moritz K; Moeder, Wolfgang; Yoshioka, Keiko; Van Damme, Daniël; De Smet, Ive; et al.
Abstract: Much of what we know about the role of auxin in plant development derives from exogenous manipulations of auxin distribution and signaling, using inhibitors, auxins, and auxin analogs. In this context, synthetic auxin analogs, such as 1-naphthalene acetic acid (1-NAA), are often favored over the endogenous auxin, indole-3-acetic acid (IAA), in part due to their higher stability. While such auxin analogs have proven instrumental in revealing the various faces of auxin, they display in some cases bioactivities distinct from IAA. Here, we focused on the effect of auxin analogs on the accumulation of PIN proteins in brefeldin A-sensitive endosomal aggregations (BFA bodies), and correlation with the ability to elicit Ca 2+ responses. For a set of commonly used auxin analogs, we evaluated if auxin analog-induced Ca 2+ signaling inhibits PIN accumulation. Not all auxin analogs elicited a Ca 2+ response, and their differential ability to elicit Ca 2+ responses correlated partially with their ability to inhibit BFA-body formation. However, in tir1/afb and cngc14, 1-NAA-induced Ca 2+ signaling was strongly impaired, yet 1-NAA still could inhibit PIN accumulation in BFA bodies. This demonstrates that TIR1/AFB–CNGC14-dependent Ca 2+ signaling does not inhibit BFA body formation in Arabidopsis roots. Abstract : Synthetic auxin analog-induced Ca 2+ signaling is independent of inhibition of PIN accumulation in brefeldin A-sensitive endosomal aggregations.